Analysis of Nidan (Etiological Factors) Of Metabolic Syndrome. - Sneha Chandankar1 , Vaishali Kuchewar2 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Metabolic syndrome is a clustering of at least three of these-Abdominal (central) obesity, Elevated bloodpressure, Elevated fasting plasma glucose, High serum triglycerides and Low high-density lipoprotein (HDL)levels. In recent years, there is an alarming increase in metabolic syndrome. The overall prevalence rate ofmetabolic syndrome is 33.5%. It is 24.9% in males and 42.3% in females. The terminology ‘Metabolicsyndrome’ represents its relation with metabolism. It can be said that disequilibrium of metabolism causesmetabolic syndrome. The word metabolism can be correlated with ‘concept of Agni’ described in Ayurvedabecause entire range of digestive and metabolic activities of the body take place with the help of the biologicalfire of the body called Agni. This study was conducted to explore the nidan (Etiological factors) of metabolicsyndrome based on basic concepts of Ayurveda and it suggest to think about overcoming mental stress (asone of the prominent etiological factor) while managing Metabolic syndrome.